Laundry Service Business Management - Arippudin, Aris (International Publisher (YAPENBI), 2022)
The purpose of this study is to find out how to manage the laundry service business, to find out what obstacles occur when managing the laundry service business, to find out the solutions used to overcome the obstacles that occur when managing the laundry service business. The research methodology used is descriptive qualitative which aims to describe the conditions and analyze the production administration process in metal metal companies. This research requires data related to the author's study which is sourced from literature studies, field studies, documentation techniques. The results of the research regarding the management carried out by entrepreneurs for their own business are quite good, both from the management in the marketing aspect, including service selection, business location determination, pricing and promotion. The financial aspect, which consists of initial capital and operational costs, is also good, as can be seen from the return on investment BEP that is obtained, but the management of human resources is still not good. Based on the observations made by the author that there are still some obstacles that can hinder business management and operational activities, such as the difficulty of maintaining HR loyalty, lack of HR in operational activities, promotion techniques that are still simple such as banners. So to overcome these obstacles the solution is to provide good welfare for its employees, as well as add employees to speed up operational activities, carry out other promotions such as using brochures and online media, and methods of picking up the ball.